(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women education in India is a major concentrated issue of the government and civil society because an educated women may play a vital role in the progress our country. Education is the milestone of women empowerment because it make capable them to responds the various type of challenges and change their life. That is why we should not neglect the significance of education in reference to women empowerment. India’s aim to becoming superpower and a developed country by 2020 could not fulfill until the upliftment of women section of society. In India the growth of women’s education in rural parts is going very slow. It means that the most part of women section officer are illiterate in our country so they are week, backward and exploited mostly. To overcome this situation education is the most effective tool of change their position and status in society. It also bring Vital change in inequalities and functions as a means of improving their positions within the family also.